El controvertido ‘derecho’ de residencia de los nacionales turcos en la Unión Europea: La STJUE de 15 noviembre 2011 (asunto Dereci) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2012)
The present study addresses the status of Turkish nationals in the European Union, following the ruling of the ECJ, dated November 15, 2011, in Case C-256/11, M. Dereci and others v. Bundesministerium für Inneres. In this decision, the ECJ defines with greater precision the content and limits of the obligations imposed on such nationals to Member States regulations deriving from the Association Agreement signed in 1963 between the European Community and Turkey. Focusing its analysis on this approach, the ECJ also sidesteps the question posed-of-the possible extension of the rights of European citizenship to non-EU family members of citizens of the Union.